Early methods of studying kazakh stories fundamentals of modern methods (Journal of Educational Sciences, 2021)
The article reveals the methodological possibilities under the works of Zh.Aimauytov in the study of modern Kazakh stories. The scientific and theoretical significance of the methods end techniques in the modern educational process, studied at the beginning of the 20th century, will be substantiated. The suggested essay writing techniques are also the foundations of the methods used by traditional and modern teaching systems.First of all, in his work “How to teach your native language? “one of the” strongest methods “ that students should use in their daily lessons is different in that it reminds them of the four language skills (lis- tening, speaking, reading, writing) that shape the student’s speech. It is considered that the opinion of J. Aimautova on the skills of forming the speech activity of students in tune with modern dialogic learning. The methodologist analyzes the continuity of the proposed methods of teaching the scientist’s stories with the existing new methods. The author examines the opinion of Zh. Aymautov that every teacher should choose methods depending on the type of story being studied. The point is that the proposed methods of writing works are also the basis of the methods that I use in the traditional system. Thus, the article systematically analyzes the research works of Zh.Aimauytov related to teaching and upbringing from the point of view of scientific pedagogy are relevant in the modern learning process. The named methodological studies are acceptable without the teaching of modern Kazakh stories in the context of the updated content of education.Key words: teaching method, approach, dialogic learning, critical thinking, skills, artwork, etc.